Charred Lullabies : Chapters in an Anthropography of Violence. - Daniel, E. Valentine (Princeton University Press, 2001)
How does an ethnographer write about violence? How can he make sense of violent acts, for himself and for his readers, without compromising its sheer excess and its meaning-defying core? How can he remain a scholarly observer when the country of his birth is engulfed by terror? These are some of the questions that engage Valentine Daniel in this exploration of life and death in contemporary Sri Lanka. In 1983 Daniel "walked into the ashes and mortal residue" of the violence that had occurred in his homeland. His planned project--the study of women's folk songs as ethnohistory--was immediately.